The patient perspective on diversity-sensitive care: a systematic review - Ewout Daniël Lieven Lauwers; Robin Vandecasteele; Michael McMahon; Stéphanie De Maesschalck; Sara Willems (International Journal for Equity in Health, 2024)
Abstract Background The provision of diversity-sensitive care is a promising approach towards reducing health disparities. Recent criticism and a scientific gap demonstrate the need for the patient perspective on diversity-sensitive care. This systematic review aims to describe the patient perspective, including patient experiences, expectations, and satisfaction with diversity-sensitive care provided by healthcare providers. Methods In December 2022 the Medline ALL, Embase, Web of Science Core Collection, Cochrane Central Register of Controlled Trials, CINAHL, PsycINFO and additionally Google Scholar were searched for original studies that described or measured patient expectations, experiences, and/or satisfaction, specifically focusing on cultural or diversity competence of healthcare providers. Analysis of the collected data was performed using a convergent mixed-methods design based on thematic synthesis. Results From initially 5,387 articles, 117 were selected for full-text screening, and ultimately, 34 articles were included in this study. The concept of diversity-sensitive care was observed to comprise three components. The first component is focused on patient-centered care and includes competencies such as clear and direct communication, shared decision-making, individualized care, empathy, and consideration. The second component centers on providing culturally tailored information, adjusting care to cultural needs, working with interpreters, allyship, community partnerships, self-awareness, and cultural knowledge, and builds upon the first component. Across the first two components of diversity-sensitive care, patients have reported experiencing dissatisfaction and encountering shortcomings in their healthcare providers, sometimes resulting in the third and final component pertaining to provider care. This component underscores the importance of linguistic, ethnic, cultural, and gender concordance in delivering quality care. Conclusion In conclusion, the patient perspective on diversity-sensitive care encompasses multiple components, from patient-centered care to concordant care. The components incorporate various competencies as communication skills, empathy, self-awareness and adjusting care to cultural needs. Patients reported experiencing dissatisfaction and shortcomings across all components of diversity-sensitive care provided by healthcare providers.